To w ' ' to ma być w ułamku
e. { '2(x+y)/3'+8=4/3(2x-y)-'x-2y/2' to w () koo kreski ułamkowej

e. { '2(x+y)/3'+8=4/3(2x-y)-'x-2y/2
'x+1/3'+1='3-y/4'

f. { x/2+y/4=2x+3y-1/2
x(y-x)-6=y(x-1)-x(x+2)

/- kreska ułamkowa
{-te klamerki maja być na 2 lenijki;P;P

1

Odpowiedzi

2010-01-06T12:10:08+01:00
2/3(x+y)+4/3(2x-y)-x-2y/2 (*6)(wszystko pomnożyć przez 6
x+1/3+1=3-y/4 (*12) (razy 12)

6(2x+2y)/3+6*8=6(8x-4y)/3-(x-2y)*6/2 (skracamy 6 z mianownikiem)
12(x+1)/3+12*1=12(3-y)/4 (skracamy 12z mianownikiem)

2(2x+2y)+48=2(8x-4y)-3x-6y
4(x+1)+12=3(3-y)

4x+4y+48=16x-8y-3x-6y
4x+4+12=6-3y


4x-16x+3x=-8y-6y-4y-48
3y=6-4x-4-12

-9x=-18y-48
3y=-10-4x

x=2+48/9
y=-10/3-4/3x

x=7 3/9
y=-10/3-4/3(66/9)

x=7 3/9
y=-10/3-88/9

x=7 3/9
y=-30/9-88/9

x=7 3/9
y=-118/9

x=7 3/9
y=-13 1/9